Defining and Classifying Economic Categories in Scientific Research on Contemporary Financial Phenomena - Krzywda, Danuta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
Scientific research on contemporary financial phenomena requires the use of information about economic categories, a significant part of which is disclosed in financial statements. High quality research is contingent upon the cohesion of the definitions used and the classification of economic categories.The main purpose of this paper is to draw the attention of theoreticians of finance, law and accounting to the need to intensify research geared to improving or creating a new definition and classification of the economic categories disclosed in the financial statements of accounting entities.To justify this thesis, the paper offers an analysis of the current state of financial statements drawn up according to IFRS and the Polish accounting law. It focuses on information about income and costs as well as the use of the term ”financial activity” at the normative, educational and economic level. The reasons for misunderstandings in this field are discussed, as are the results of those misunderstandings. This may help in the production of research aimed preventing both, and thus at improving the creation of crucial information for the development of theory of law and economic practice.